PROSPECTS FOR ENSURING THE INTEGRATION OF SCIENCE, EDUCATION, AND PRODUCTION IN A DIGITAL ENVIRONMENT - Karimova Shirin Zoxid qizi; Xidirova Barchinoy Ilxomovna (Modern American Journals, 2025)
The article explores the prospects for integrating science, education, and industry within a unified digital environment. It highlights the growing need for seamless collaboration among these sectors in light of accelerating technological advancement. As digital tools reshape the way knowledge is created, shared, and applied, stronger connections between universities, research institutions, and industrial enterprises become vital. The study discusses how digital ecosystems and platform-based models can serve as effective frameworks for such integration. Special emphasis is placed on adapting these approaches to the context of Uzbekistan, where bridging the gap between academic knowledge and practical implementation remains a pressing issue. The article concludes by offering strategic insights that can help reinforce national innovation systems through enhanced cooperation between science, education, and production.
Keywords: Digital ecosystems, commercialization of scientific knowledge, innovation, artificial intelligence, big data, blockchain, IoT, integration, science and industry, Uzbekistan.